2021
DOI: 10.3389/fcell.2021.720782
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ARL3 Gene Mutation Associated With Autosomal Dominant Retinal Degeneration

Abstract: Despite major progress in the discovery of causative genes, many individuals and families with inherited retinal degenerations (IRDs) remain without a molecular diagnosis. We applied whole exome sequencing to identify the genetic cause in a family with an autosomal dominant IRD. Eye examinations were performed and affected patients were studied with electroretinography and kinetic and chromatic static perimetry. Sequence variants were analyzed in genes (n = 271) associated with IRDs listed on the RetNet databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…In photoreceptors, Arl3 regulates enrichment of many lipidated proteins essential for eliciting the visual response within the outer segment, a modified primary cilium (reviewed in Frederick et al, 2020 ). Recently, human mutations in Arl3 have been linked to various forms of retinal degeneration: R99I causes autosomal recessive cone-rod dystrophy ( Sheikh et al, 2019 ), R149H or R149C cause recessive Joubert syndrome ( Alkanderi et al, 2018 ), compound heterozygous T31A/C118F causes rod-cone dystrophy ( Fu et al, 2021 ), Y90C causes autosomal dominant retinitis pigmentosa ( Holtan et al, 2019 ; Strom et al, 2016 ), and D67V causes autosomal dominant retinal degeneration ( Ratnapriya et al, 2021 ). The R149H/C mutation is present at the Arl3–Arl13B interface and was shown to prevent Arl3 activation by Arl13B, which causes reduced enrichment of lipidated proteins in the cilium ( Alkanderi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In photoreceptors, Arl3 regulates enrichment of many lipidated proteins essential for eliciting the visual response within the outer segment, a modified primary cilium (reviewed in Frederick et al, 2020 ). Recently, human mutations in Arl3 have been linked to various forms of retinal degeneration: R99I causes autosomal recessive cone-rod dystrophy ( Sheikh et al, 2019 ), R149H or R149C cause recessive Joubert syndrome ( Alkanderi et al, 2018 ), compound heterozygous T31A/C118F causes rod-cone dystrophy ( Fu et al, 2021 ), Y90C causes autosomal dominant retinitis pigmentosa ( Holtan et al, 2019 ; Strom et al, 2016 ), and D67V causes autosomal dominant retinal degeneration ( Ratnapriya et al, 2021 ). The R149H/C mutation is present at the Arl3–Arl13B interface and was shown to prevent Arl3 activation by Arl13B, which causes reduced enrichment of lipidated proteins in the cilium ( Alkanderi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, over the past few years, there has been a growing interest in the development of small-molecule DUB inhibitors as therapeutic agents, mainly to treat cancer [ 66 ]. Our results indicate that USP48 inhibition might be a good therapeutic strategy to counteract the effect of ARL3 variants causing autosomal dominant RP [ 67 , 68 ], but further research is needed since, to the best of our knowledge, no USP48-specific inhibitor has been developed so far.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in silico analyses predicted that the D67V mutation would decrease affinity to the Arl3 binding partners RP2, UNC119a, and Arl13B (Ratnapriya et al, 2021). In fact, we found that Arl3-D67V forms a stable complex with RP2, like the constitutively active Q71L variant (Fig 3C); but appears to subtly change the binding properties toward the effectors PDEδ and UNC119.…”
Section: Discussionmentioning
confidence: 99%
“…A recent flurry of papers identified multiple Arl3 variants that cause either dominant or recessive retinal disease (Strom et al, 2016; Alkanderi et al, 2018; Holtan et al, 2019; Sheikh et al, 2019; Fu et al, 2021; Ratnapriya et al, 2021). These studies highlighted the necessity of Arl3 for photoreceptor health and raised the possibly that different biochemical alterations in Arl3 might produce divergent pathobiological underpinnings.…”
Section: Discussionmentioning
confidence: 99%